Food nutrition and health in the Caribbean - a time for re-examination - Sinha, Dinesh P. (CFNI KingstonJM, 1995)
Re-examines food availability, nutrition and health in the contemporary Caribbean in the light of the newer scientific knowledge which has become available in the last thirty years.